A Place for the People : the story of a national library - Seet, K.K
No longer can one describe a national library as merely the proserver of the cultural heritage and the cnter of bibliographical services. These functions will still be theirs, but increasingly the true 'national' library will support the goals of the nation, whatever they may be.